Inflammation and Immune Response in COPD: Where Do We Stand? - Nikoletta Rovina; Antonia Koutsoukou; Nikolaos G. Koulouris (Mediators of Inflammation)
Increasing evidence indicates that chronic inflammatory and immune responses play key roles in the development and progression of COPD. Recent data provide evidence for a role in the NLRP3 inflammasome in the airway inflammation observed in COPD. Cigarette smoke activates innate immune cells by triggering pattern recognition receptors (PRRs) to release “danger signal”. These signals act as ligands to Toll-like receptors (TLRs), triggering the production of cytokines and inducing innate inflammation. In smokers who develop COPD there appears to be a specific pattern of inflammation in the airways and parenchyma as a result of both innate and adaptive immune responses, with the predominance of CD8+ and CD4+ cells, and in the more severe disease, with the presence of lymphoid follicles containing B lymphocytes and T cells. Furthermore, viral and bacterial infections interfere with the chronic inflammation seen in stable COPD and exacerbations via pathogen-associated molecular patterns (PAMPs). Finally, autoimmunity is another novel aspect that may play a critical role in the pathogenesis of COPD. This review is un update of the currently discussed roles of inflammatory and immune responses in the pathogenesis of COPD.